Burning hay as a tool in conservation of mountain grassland vegetation in protected areas - Jan Zarzycki (Acta Scientiarum Polonorum. Formatio Circumiectus)
In some areas of Polish Carpathians high nature value grasslands are managed only because of agri-environmental subsidies or as an active preservation measures in protected areas. Due to the abandonment of livestock farming the problem is the dispose of collected biomass. In the Pieniny National Park in some cases the hay harvested and collected in pile is burned. The aim of the study was to evaluate the impact of the burning of a large amount of hay on vegetation and assess the possibility of using this measure in preservation of species rich plant communities. In 1997 piles of hay were burned on 17 plots. On the burned plots plant and soil analysis were determined in years 1998–2001 and repeated in 2014. During the first four years there was a significant increase in the content of available phosphorus, potassium and soil pH. As a result, at the beginning, increased growth of legumes, was observed. Next, the grass species began to appear in greater number. After 17 years soil parameters of burnt plots were similar to that of surrounding areas and no considerable differences in plant composition was observed. However, some of burnt plots were still distinguishable on the meadow. Under certain conditions, the burning of hay can be used in management of grassland.